Alkali-activated cementing material as well as preparation method and application thereof
By adjusting the ratio of water glass to NaOH and the combination of iron tailings sand, limestone and fly ash, an alkali-activated cementitious material with good mechanical properties was prepared, which solved the problem of unstable performance in the preparation of various solid waste materials and achieved improvements in environmental protection and cost-effectiveness.
Patent Information
- Application Number
- CN202511521739.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-01-13
AI Technical Summary
In existing technologies, when preparing alkali-activated cementitious materials from various solid waste materials, the mechanical properties are poor and difficult to control, posing a risk of performance fluctuations and resulting in unstable product performance.
A composite alkali activator was used to prepare alkali-activated cementitious materials by mixing water glass and NaOH, combined with iron tailings sand, limestone and fly ash. By adjusting the mass ratio of the raw materials to 2000:350-520 and 70-80:30-40, alkali-activated cementitious materials with good mechanical properties were prepared.
By adjusting the proportion of raw materials, an alkali-activated cementitious material with good mechanical properties was prepared, which broadened the disposal methods of solid waste materials, reduced construction costs, and could be used for underground filling and roadbed subbase materials, reducing cement consumption and having environmental advantages.
Smart Images

Figure CN121318253A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of green gel materials, and particularly relates to an alkali-activated gel material and a preparation method and application thereof. BACKGROUND
[0002] In the construction industry, cement occupies an important position, but a large amount of greenhouse gases is emitted in the production process of cement, which accelerates global warming. In order to reduce the emission of greenhouse gases, it is essential to develop new green gel materials.
[0003] The alkali-activated gel material is a kind of inorganic material formed by chemical reaction through alkali-activated agent to activate aluminosilicate precursor, which has gel properties. The core feature is to replace the hydration process of traditional cement by chemical action in alkali environment, which has the advantages of high performance and environmental protection.
[0004] At present, solid waste materials are generally used to prepare alkali-activated gel materials, and different sources and types of solid waste can complement each other. However, the chemical composition, mineral phase and physical properties of solid waste will greatly affect the performance of alkali-activated gel materials.
[0005] An important point is the composition ratio of solid waste materials, and the combination of different types of solid waste materials increases the uncertainty of alkali-activated gel materials, resulting in a higher risk of performance fluctuation of the final product than single material. More importantly, the product phase formed by mixing multiple solid waste materials with water is often more complex. Different types of solid waste materials have different requirements for the composition ratio of alkali-activated agent. In multiple solid waste materials, the gel material is formed by alkali-activated agent. Due to the complex interaction between alkali-activated agent and multiple solid waste materials, the reaction product phase may be more mixed, making it more difficult to predict and control the performance, and there is a risk of variability. The mechanical properties of the alkali-activated gel material prepared by the prior art through multiple solid waste materials are poor. SUMMARY
[0006] The technical problem to be solved by the present application is how to prepare an alkali-activated gel material with good mechanical properties.
[0007] The present application solves the above technical problems by the following technical means: The present application provides an alkali-activated gel material in the first aspect, which comprises a composite alkali activator and a solid waste gel material; the composite alkali activator is mixed by water glass and NaOH, and the mass ratio of water glass to NaOH is 2000:350-520; the solid waste gel material is mixed by iron tailings sand, limestone and fly ash, wherein the mass ratio of the total mass of limestone and fly ash to the mass of iron tailings sand is 70-80:30-40; the mass ratio of the composite alkali activator to the solid waste gel material is 0.32-0.38:1.
[0008] Beneficial effects: This invention prepares alkali-activated cementitious materials by co-processing iron tailings sand with limestone and fly ash. By controlling the mass ratio of raw materials, alkali-activated cementitious materials with good mechanical properties can be obtained.
[0009] Preferably, the fly ash accounts for 20% to 30% of the total mass of limestone and fly ash.
[0010] Beneficial effects: This invention further controls the mass percentage of fly ash in the total mass of limestone and fly ash to obtain an alkali-activated cementitious material with good mechanical properties.
[0011] Preferably, the iron tailings sand has the following chemical composition and mass percentage: Fe2O3 40%–45%, SiO2 15%–25%, CaO 10%–15%, Al2O3 5%–10%, MgO 2%–3%, SO3 4%–5%, K2O 0%–1%, P2O5 1%–2%, with the balance being Fe.
[0012] Preferably, the limestone has the following chemical composition and mass percentage: CaO 95%–98%, MgO 1%–3%, SiO2 0–0.5%, Fe2O3 0–0.5%, Al2O3 0–0.5%, SO3 0–0.05%, K2O 0–0.05%, with the balance being Ca.
[0013] Preferably, the fly ash has the following chemical composition and mass percentage: 40%–50% SiO2, 30%–40% Al2O3, 3%–6% Fe2O3, 1%–3% CaO, 0–1% MgO, 0–0.5% P2O5, 1%–2% SO3, 1%–2% K2O, with the balance being SO3.
[0014] Preferably, the iron tailings sand has a D10 of 85μm to 90μm, a D50 of 210μm to 215μm, and a D90 of 535μm to 540μm.
[0015] Preferably, the limestone has a D10 of 5μm to 8μm, a D50 of 16μm to 19μm, and a D90 of 42μm to 44μm.
[0016] Preferably, the fly ash has a D10 of 11μm to 14μm, a D50 of 68μm to 70μm, and a D90 of 690μm to 692μm.
[0017] Beneficial effects: The present invention further limits the particle size of iron tailings sand, limestone and fly ash. The smaller the particle size, the larger the specific surface area, the higher the degree of chemical reaction participation of iron tailings sand, limestone and fly ash, the stronger the potential adhesive properties, the more products generated, the higher the strength, and the better the mechanical properties of alkali-activated cementitious materials.
[0018] Preferably, the total mass ratio of the limestone and fly ash to the iron tailings sand is 77:33.
[0019] The second aspect of the present invention provides a method for preparing the above-mentioned alkali-activated gelling material, wherein a composite alkali activator and a solid waste gel material are mixed evenly to obtain the alkali-activated gelling material.
[0020] The third aspect of the present invention provides the application of the above-mentioned alkali-activated cementitious material as an underground filling material or a roadbed subbase material.
[0021] Preferably, the alkali-activated cementitious material is mixed with water to obtain a polymer slurry, which is then poured into the ground or roadbed for curing.
[0022] Preferably, the maintenance period is 14 to 28 days.
[0023] Beneficial effects: The alkali-activated cementitious material of this invention has good mechanical properties. It is made from three solid waste materials, which broadens the methods for solid waste disposal and can reduce construction costs. The alkali-activated cementitious material can be used as an underground filling material, which can reduce the amount of cement used and is beneficial to environmental protection. The alkali-activated cementitious material can also be used as a subgrade material, which can significantly reduce costs and improve efficiency. Attached Figure Description
[0024] Figure 1 This is a ternary phase diagram of the chemical composition of iron tailings sand, limestone and fly ash in this invention; Figure 2 This is a mineral phase diagram of iron tailings sand, limestone and fly ash in this invention; Figure 3 These are scanning electron microscope (SEM) and laser particle size distribution images of iron tailings sand, limestone, and fly ash in Embodiment 1 of the present invention; wherein, (a) and (b) are SEM and laser particle size distribution images of iron tailings sand; (c) and (d) are SEM and laser particle size distribution images of limestone; and (e) and (f) are SEM and laser particle size distribution images of fly ash. Figure 4 This is a flowchart of the sample preparation process in an embodiment of the present invention; Figure 5 The modulus of the activator in Experiment Example 1 M Alkali-to-solid ratio A / P Water-to-glue ratio W / Cand FA doping ω The corresponding factors K i , k i Bar chart; where (a) is the modulus of the activator. M (b) is the alkali-to-solid ratio. A / P (c) is the water-to-glue ratio. W / C (d) represents the FA doping amount. ω ; Figure 6 This refers to the experimental example 1, under different ages and different factors. k i Distribution trend chart; Figure 7 These are the XRD patterns of the 1-day-old samples from Examples 4-6 and Comparative Example 7; Figure 8 These are the XRD patterns of the 7-day-old samples from Examples 4-6 and Comparative Example 7; Figure 9 These are the XRD patterns of the 14-day-old samples from Examples 4-6 and Comparative Example 7; Figure 10 These are SEM images of the samples from Examples 4-6 and Comparative Example 7; where (a)(b)(c) are SEM images of the sample from Example 4 at 1 day, 7 days, and 14 days; (d)(e)(f) are SEM images of the sample from Example 5 at 1 day, 7 days, and 14 days; (g)(h)(i) are SEM images of the sample from Example 6 at 1 day, 7 days, and 14 days; and (j)(k)(l) are SEM images of the sample from Comparative Example 7 at 1 day, 7 days, and 14 days. Figure 11 These are FTIR images of 1-day-old samples from Examples 4-6 and Comparative Example 7; Figure 12 These are FTIR images of the 7-day-old samples from Examples 4-6 and Comparative Example 7; Figure 13 These are FTIR images of the 14-day-old samples from Examples 4-6 and Comparative Example 7; Figure 14 This is the BET plot of the 14-day-old sample in Example 4; Figure 15 This is the BET plot of the 14-day-old sample in Comparative Example 7. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0027] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0028] In the examples and comparative examples, IOT represents iron tailings, LSP represents limestone, and FA represents fly ash. The ternary phase diagram of iron tailings, limestone, and fly ash is shown below. Figure 1 As shown, its chemical composition is as follows:
[0029] Mineral phase diagrams of iron tailings sand, limestone, and fly ash are shown below. Figure 2 As shown in the figure, the mineral phases inside the iron tailings sand are mainly quartz and hematite. The fly ash exhibits a distinct hump at 2θ of approximately 18-27°, displaying an amorphous shape, indicating that the fly ash has high pozzolanic properties. The limestone shows no other disordered diffraction peaks and is dominated by calcite.
[0030] Example 1 according to Figure 4 As shown in the figure, this embodiment provides an alkali-activated cementitious material, its preparation method, and its application, as detailed below: S1 Preparation of Composite Alkali Activator A composite alkali activator was obtained by mixing 2000g of water glass with 394.4g of NaOH. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.2.
[0031] S2 Preparation of Solid Waste Gel Materials The iron tailings sand weighs 330g, the limestone weighs 616g, and the fly ash weighs 154g. The iron tailings sand, limestone, and fly ash are then mixed and stirred evenly to obtain a solid waste gel material. The total mass ratio of limestone and fly ash to iron tailings sand is 77:33, with fly ash accounting for 20% of the total mass of limestone and fly ash.
[0032] exist Figure 3 In China, according to Figure 3As can be seen from electron microscopy, the iron tailings sand exhibits a mixture of large and small particles, with uneven particle distribution and highly irregular shapes, mostly appearing as angular lumps. Some particles have relatively smooth surfaces. Figure 3 As can be seen from b, the D10, D50, and D90 of the iron tailings sand are 89.08, 212.1, and 536.8 μm, respectively, and its specific surface area is 130.9 cm². 2 / g.
[0033] according to Figure 3 c shows that limestone is finely crushed, mostly in the form of fragments or thin flakes, with larger particles having smooth surfaces. Figure 3 As can be seen from d, the D10, D50, and D90 of limestone are 6.42, 17.9, and 43.09 μm, respectively, and its specific surface area is 1616 cm². 2 / g.
[0034] according to Figure 3 As can be seen, fly ash is a dark gray powder. The particles are relatively uniform and fine, with no obvious agglomeration. Figure 3 As can be seen from f, the D10, D50, and D90 of fly ash are 12.84, 69.43, and 691.3 μm, respectively, and its specific surface area is 625.7 cm². 2 / g.
[0035] S3 Preparation of Alkali-Activated Cementitious Materials 352g of the composite alkali activator was mixed with 1100g of solid waste gel material and stirred evenly to obtain an alkali-activated gelling material. The mass ratio of the composite alkali activator to the solid waste gel material was 0.32:1.
[0036] Application of S4 Alkali-Activated Cementitious Materials Alkali-activated gelling material was uniformly mixed with water to obtain a polymer slurry. The mass of the solid waste gelling material was 1100g, and the mass of water was 217.25g, with a water-to-solid-waste gelling material mass ratio of 0.26:1. The polymer slurry was poured into a gel mold, sealed with plastic wrap, and placed in a standard curing chamber (relative humidity 95%, temperature 25℃) for 24 hours. After 24 hours of curing, the mold was removed, and curing continued until 3, 7, 14, and 28 days of age, obtaining samples at 3, 7, 14, and 28 days of age.
[0037] Example 2 The difference between Example 2 and Example 1 is that the mass ratio of the composite alkali activator to the solid waste gel material is 0.35:1, the fly ash accounts for 25% of the total mass of limestone and fly ash, and the mass ratio of water to the solid waste gel material is 0.28:1.
[0038] Example 3 The difference between Example 3 and Example 1 is that the mass ratio of the composite alkali activator to the solid waste gel material is 0.38:1, the fly ash accounts for 30% of the total mass of limestone and fly ash, and the mass ratio of water to the solid waste gel material is 0.30:1.
[0039] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that 2000g of water glass and 346.4g of NaOH were mixed to obtain a composite alkali activator. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.3.
[0040] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that 2000g of water glass and 346.4g of NaOH were mixed to obtain a composite alkali activator. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.3.
[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that 2000g of water glass and 346.4g of NaOH were mixed to obtain a composite alkali activator. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.3.
[0042] Comparative Example 4 Compared with Example 1, Comparative Example 4 differs in that 2000g of water glass and 305.2g of NaOH are mixed to obtain a composite alkali activator. The purity of the NaOH is 96%, and the mass ratio of SiO2 to Na2O is approximately 1.4.
[0043] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that 2000g of water glass and 305.2g of NaOH were mixed to obtain a composite alkali activator, wherein the purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.4.
[0044] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that 2000g of water glass and 305.2g of NaOH were mixed to obtain a composite alkali activator, wherein the purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.4.
[0045] The differences between Examples 2 and 3 and Comparative Examples 1-6 are shown in Table 2. All other aspects are the same as in Example 1.
[0046] Experimental Example 1 This experimental example uses a three-level, four-factor orthogonal experimental design to investigate the modulus of the activator. M Alkali-to-solid ratio A / P , FA dosage ω Water-to-glue ratio W / C The influence of different curing ages on mechanical properties is shown in Table 1, with specific orthogonal experimental schemes. The modulus of the activator is also described. M This represents the mass ratio of SiO2 to Na2O. The FA doping amount... ω This indicates the percentage of fly ash in the total mass of limestone and fly ash. The alkali-to-solid ratio A / P represents the mass ratio of the composite alkali activator to the solid waste gel material. The water-to-binder ratio... W / C This represents the mass ratio of water to solid waste gel material.
[0047] Unconfined compressive strength was measured on some specimens from the orthogonal experiment, and the compressive strengths are shown in Table 2. The compressive strengths were then summarized and calculated. K i , k i , R M The activator modulus was obtained for each age period. M Alkali-to-solid ratio A / P , FA dosage ω Water-to-glue ratio W / C The order of influence and the optimal combination ratio in orthogonal experiments, specifically as follows: Figure 5 As shown in Figure 1 and Table 3.
[0048] Table 1 Orthogonal Experiment Scheme
[0049] Table 2 Compressive Strength of Orthogonal Tests
[0050] Table 3 Orthogonal Experiment R M
[0051] according to Figure 5 It can be seen that at different ages, different influencing factors... K i , k i The trend of value change, through Figure 5 Combining this with Table 3, we can conclude that the degree of influence on mechanical properties is as follows: activator modulusM >The alkali-to-solid ratio is A / P >FA dosage ω > Water-to-glue ratio W / C .
[0052] according to Figure 6 It can be seen that the optimal ratio in the orthogonal experiment is specifically: activator modulus M The alkali-to-solid ratio is 1.2. A / P 0.38, FA doping ω The water-to-binder ratio is 30%. W / C It is 0.26.
[0053] Example 4 according to Figure 4 As shown in the figure, this embodiment provides an alkali-activated cementitious material, its preparation method, and its application, as detailed below: S1 Preparation of Composite Alkali Activator A composite alkali activator was obtained by mixing 2000g of water glass with 519g of NaOH. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.0.
[0054] S2 Preparation of Solid Waste Gel Materials The iron tailings sand weighs 330g, the limestone weighs 539g, and the fly ash weighs 231g. The iron tailings sand, limestone, and fly ash are then mixed and stirred evenly to obtain a solid waste gel material. The total mass ratio of limestone and fly ash to iron tailings sand is 77:33, with fly ash accounting for 30% of the total mass of limestone and fly ash.
[0055] S3 Preparation of Alkali-Activated Cementitious Materials 418g of the composite alkali activator and 1100g of solid waste gel material were mixed and stirred evenly to obtain an alkali-activated gelling material. The mass ratio of the composite alkali activator to the solid waste gel material was 0.38:1.
[0056] Application of S4 Alkali-Activated Cementitious Materials Alkali-activated gelling material was uniformly mixed with water to obtain a polymer slurry. The mass of the solid waste gelling material was 1100g, and the mass of water was 215.90g, with a water-to-solid waste gelling material mass ratio of 0.26:1. The polymer slurry was poured into a gel mold, sealed with plastic wrap, and placed in a standard curing chamber (relative humidity 95%, temperature 25℃) for 24 hours. After 24 hours of curing, the mold was removed, and curing continued until 1, 7, and 14 days of age to obtain samples at 1, 7, and 14 days of age.
[0057] Example 5 The difference between Example 5 and Example 4 is that 2000g of water glass and 415g of NaOH are mixed to obtain a composite alkali activator, wherein the purity of NaOH is 96%, and the mass ratio of SiO2 to Na2O is approximately 1.1.
[0058] Example 6 The difference between Example 6 and Example 4 is that 2000g of water glass and 394.4g of NaOH are mixed to obtain a composite alkali activator. The purity of the NaOH is 96%, and the mass ratio of SiO2 to Na2O is approximately 1.2.
[0059] Comparative Example 7 The difference between Comparative Example 7 and Example 4 is that 2000g of water glass and 346.4g of NaOH were mixed to obtain a composite alkali activator. The purity of the NaOH was 96%, and the mass ratio of SiO2 to Na2O was approximately 1.3.
[0060] The differences between Examples 5 and 6 and Comparative Example 7 are shown in Table 4, while all other aspects are the same as in Example 4.
[0061] Comparative Example 8 This comparative example provides a Portland cement manufactured by Anhui Conch Cement Co., Ltd.
[0062] Experiment Example 2 As shown in Experiment 1, the activator modulus has the greatest impact on mechanical properties. M This experimental example focuses on the modulus of the activator. M Single-factor experiments were conducted to investigate the influence of the most influential factors on the mechanical properties under early-age conditions. The experimental schemes are shown in Table 4. Specifically, the experimental schemes are Examples 4-6 and Comparative Example 7. The specimens obtained from these experiments were subjected to unconfined compressive strength tests, and the compressive strengths are shown in Table 5.
[0063] Table 4 Single-factor experimental design
[0064] Table 5 Compressive strength in single-factor tests
[0065] The samples from Examples 4-6 and Comparative Example 7 were subjected to microscopic tests, as detailed below: (1) XRD experimental analysis and reaction mechanism At 1, 7, and 14 days of curing, blocky samples from the cross-section were taken and dried in a 60℃ drying oven for 10 hours. The samples were then ground in an agate mortar until they passed through a 200-mesh sieve, sealed in bags, and subjected to XRD testing using a Bruker D8 Advance X-ray diffractometer (Germany). The samples were pulverized and passed through a 0.075mm sieve, then placed on a rotating stage and scanned from 5° to 80° with a scanning step of 0.01° and a scanning speed of 10° / min. (Details follow...) Figures 7-9 As shown in the figure, the horizontal axis represents the XRD test scanning range, and the vertical axis represents the peak height.
[0066] The introduction of reactive mineral phases promotes gel formation and is beneficial for early strength development; conversely, the introduction of inert mineral phases has a negative impact, causing the sample strength to decrease over time. By controlling the composition of the reactive materials, the formation of hydration products can be controlled, the microstructure of alkali-activated cementitious materials can be optimized, and thus their macroscopic mechanical properties can be improved. Figures 7-9 A hematite (Fe2O3) diffraction peak (PDF#47-1409, crystal plane 100) was still observed at 47.31°. This indicates that the hematite contained in IOT has low activity in strongly alkaline solutions and mainly exists as an inert filler, not participating in the polymerization reaction.
[0067] (2) SEM experimental analysis and reaction mechanism The XRD analysis revealed that when the composite alkali activator was mixed with the solid waste cementitious material, a polymerization reaction occurred, generating a series of cementitious products. After the unconfined compressive strength test, small blocky samples from the natural cross-section were taken and dried at low temperature in a 60°C oven for 10 hours. Due to the poor conductivity of fly ash, iron tailings sand, and limestone, charges accumulate on the surface, resulting in unclear electron microscopy imaging. Therefore, the samples needed to be sputter-coated with gold before electron microscopy testing. The instrument used for testing was a Pharos-SED-EDSG220023-F scanning electron microscope manufactured by Phenom GmbH, Netherlands. To clearly observe the internal microstructure of the samples, an appropriate magnification was selected for imaging during the experiment, as detailed below. Figure 10 As shown.
[0068] according to Figure 10 As shown, the sample's microstructure exhibits an uneven surface, indicating low cohesion in its microstructure. Larger fly ash particles are embedded within the gel matrix, while smaller fly ash particles adhere to the gel phase surface. Furthermore, small amounts of gel material are adsorbed on the surfaces of the IOT and LSP particles, suggesting a physical interaction between them as nucleation sites. Figure 10(h) The fly ash particles on the surface of the internal structure of the sample are adhered to by a large amount of gel material, and are almost completely wrapped by the gel material. Some tiny LSP particles are mainly distributed in the vicinity of pores and cracks, indicating that they have a filling effect. Figure 10 (k) The typical stacked sheet-like structure of hydrated calcium aluminosilicate gel (C-(A)-SH) was observed in the sample.
[0069] (3) FTIR experimental analysis and reaction mechanism When the composite alkali activator is mixed with solid waste cementitious materials, a polymerization reaction occurs, generating a series of cementitious products. After the unconfined compressive strength test, block samples from the natural cross-section are taken and dried in a 60°C drying oven for 10 hours. They are then ground in an agate mortar until they pass through a 200-mesh sieve, sealed in bags, and subjected to FTIR testing. The instrument used for subsequent testing is a Nicolet 6700 Fourier transform infrared spectrometer manufactured by Thermo Scientific, USA, to analyze changes in internal chemical bonds or functional groups. Attenuated total reflectance (ATR) method is used to test dried, anhydrous samples with a grinding fineness exceeding 200 mesh. Specifically, as follows... Figures 11-13 As shown.
[0070] according to Figures 11-13 It can be seen that the main absorption band of the polymerization product is located at 900-1050 cm⁻¹. -1 The absorption band originates from the symmetric and asymmetric stretching vibrations of the Si-OT bond (T:Si or Al tetrahedron). This spectral feature has been confirmed as an indicator of gel formation and polymerization degree. With increasing curing age and decreasing modulus, the absorption peak intensity increases and sharpens. This change is mainly attributed to the increased degree of gel polymerization and increased aluminum content, indicating that the alkali activation reaction continues throughout the experimental period. At the same curing age, the absorption band gradually shifts to lower wavenumbers as the modulus decreases, indicating that [SiO4]... 4- Groups are gradually deposited at the Si-O-Si bond sites by [AlO4]. 5- Replacement, prompting Al 3+ More effectively integrated into the polymer network. The resulting increase in internal Al 3+ The content can promote the release of some Ca from CaCO3. 2+ And Ca 2+ Increased concentration favors the progress of the base activation reaction. 580 cm -1 The broadband amplitude is attributed to Si-O bond vibrations. Samples with a modulus of 1.3 and a curing age of 1 day showed amplitudes between 900-1050 cm⁻¹. -1 The nearby spectral bands are significantly broadened, indicating that the disorder within the sample is higher than that of other samples, and the sample strength is lower.
[0071] (4) BET test analysis and reaction mechanism When the composite alkali activator is mixed with solid waste cementitious materials, a polymerization reaction occurs, generating a series of cementitious products. After the unconfined compressive strength test, block samples from the natural cross-section are taken and dried in a 60℃ drying oven for 10 hours. They are then ground in an agate mortar until they pass through a 200-mesh sieve, sealed in bags, and subjected to a BET test. Subsequent testing was performed using an Autosorb-IQ automatic specific surface area and porosity analyzer manufactured by Quanta Instruments, Inc. N2 adsorption and desorption isotherms were measured at 77K and different relative pressures. Before testing, the samples were degassed under vacuum at 200℃ for 24 hours. Based on the measured N2 adsorption-desorption isotherms, the specific surface area and pore size distribution of the corresponding samples were analyzed, as detailed below. Figures 14-15 As shown.
[0072] according to Figure 14 It can be seen that, M =1.0, the porosities of the 14d desorption curves were 19.35%, 70.97%, and 9.68%, respectively. According to Figure 15 It can be seen that, M =1.3, and the porosities of the 14d desorption curves are 16.67%, 73.33%, and 10%, respectively. M At a concentration of 1.0 and a 14-day condition, the proportion of micropores was higher than that of macropores, indicating that more pores formed in the gel and the microstructure was more compact. The pore structures of both were roughly the same, predominantly mesoporous. Calculations were performed using the BET equation. M =1.0, 14d M =1.3, 14d specific surface area (S) BET The values are 27.757 and 3.399 m respectively. 2 / g. M =1.0, the sample with a larger specific surface area at 14d indicates the formation of more gel material and a more compact internal structure.
[0073] (5) Cost comparison of Examples 4-6 and Comparative Examples 7-8 is shown in Table 6.
[0074] Table 6 Cost Comparison
[0075] As shown in Table 6, the alkali-activated cementitious material in this embodiment has more significant economic benefits compared to Portland cement.
[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An alkali-activated cementitious material, characterized in that, The raw materials include a composite alkali activator and a solid waste gel material; the composite alkali activator is a mixture of water glass and NaOH, with a mass ratio of water glass to NaOH of 2000:350-520; the solid waste gel material is a mixture of iron tailings sand, limestone, and fly ash, wherein the total mass ratio of limestone and fly ash to iron tailings sand is 70-80:30-40; and the mass ratio of the composite alkali activator to the solid waste gel material is 0.32-0.38:
1.
2. The alkali-activated cementitious material according to claim 1, characterized in that, The fly ash accounts for 20% to 30% of the total mass of limestone and fly ash.
3. The alkali-activated cementitious material according to claim 1, characterized in that, The iron tailings sand has the following chemical composition and mass percentage: Fe2O3 40%–45%, SiO2 15%–25%, CaO 10%–15%, Al2O3 5%–10%, MgO 2%–3%, SO3 4%–5%, K2O 0%–1%, P2O5 1%–2%, with the balance being Fe.
4. The alkali-activated cementitious material according to claim 1, characterized in that, The limestone has the following chemical composition and mass percentage: CaO 95%–98%, MgO 1%–3%, SiO2 0–0.5%, Fe2O3 0–0.5%, Al2O3 0–0.5%, SO3 0–0.05%, K2O 0–0.05%, with the balance being Ca.
5. The alkali-activated cementitious material according to claim 1, characterized in that, The fly ash has the following chemical composition and mass percentage: SiO2 40%–50%, Al2O3 30%–40%, Fe2O3 3%–6%, CaO 1%–3%, MgO 0–1%, P2O5 0–0.5%, SO3 1%–2%, K2O 1%–2%, with the balance being SO3.
6. The alkali-activated cementitious material according to claim 1, characterized in that, The iron tailings sand has a D10 of 85μm to 90μm, a D50 of 210μm to 215μm, and a D90 of 535μm to 540μm; the limestone has a D10 of 5μm to 8μm, a D50 of 16μm to 19μm, and a D90 of 42μm to 44μm; and the fly ash has a D10 of 11μm to 14μm, a D50 of 68μm to 70μm, and a D90 of 690μm to 692μm.
7. The method for preparing the alkali-activated cementitious material according to any one of claims 1-6, characterized in that, The composite alkali activator and solid waste gel material are mixed evenly to obtain alkali-activated gelling material.
8. The application of an alkali-activated cementitious material as described in any one of claims 1-6 as an underground filling material or a roadbed subbase material.
9. The application of the alkali-activated cementitious material according to claim 8 as an underground filling material or roadbed subbase material, characterized in that, Alkali-activated cementitious materials are mixed with water to obtain polymer slurry, which is then poured underground or onto roadbeds for curing.
10. The application of the alkali-activated cementitious material according to claim 9 as an underground filling material or roadbed subbase material, characterized in that, The maintenance period is 14 to 28 days.
Citation Information
Cited By
Quick-hardening early-strength durable ternary geopolymer engineering material and preparation method thereof
CN121651853A
A fast-hardening early-strength durable ternary geopolymer engineering material and a preparation method thereof
CN121651853B